Migrasi Internasional Penduduk Pulau Jawa Menjadi Pekerja Migran Indonesia di Luar Negeri - Fivien Muslihatinningsih; Juan Palem Sinaga; Nanik Istiyani (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2020)
International migration by Indonesian Migrant Workers (PMI) not only has a positive impact on improving the economic conditions of PMI families but also contributes to developing the country's economy through PMI remittances. This study aims to determine the effect of Unemployment, minimum wages, poverty, and human development index on international migration of Indonesian Migrant Workers (PMI) on the island of Java. This study uses secondary data in the form of panel data, with time-series data (2010 - 2019) and cross-section data (6 provinces on Java island). The data analysis method uses a panel data regression with the Common Effect Model (CEM) approach. Statistical tests use simultaneous tests, partial tests, and the coefficient of determination. This study uses the classic assumption test, the multicollinearity test, the heteroscedasticity test, and the normality test. The study results concluded that simultaneously Unemployment, minimum wages, poverty, and the human development index had a significant effect on international migration. Partially, Unemployment and poverty have a positive and significant impact, minimum wages have a negative and significant effect, while the human development index has a positive and not significant effect on international migration.